2018
DOI: 10.3390/cryst8030112
|View full text |Cite
|
Sign up to set email alerts
|

Intra-/Intermolecular Bifurcated Chalcogen Bonding in Crystal Structure of Thiazole/Thiadiazole Derived Binuclear (Diaminocarbene)PdII Complexes

Abstract: The coupling of cis-[PdCl2(CNXyl)2] (Xyl = 2,6-Me2C6H3) with 4-phenylthiazol-2-amine in molar ratio 2:3 at RT in CH2Cl2 leads to binuclear (diaminocarbene)PdII complex 3c. The complex was characterized by HRESI+-MS, 1H NMR spectroscopy, and its structure was elucidated by single-crystal XRD. Inspection of the XRD data for 3c and for three relevant earlier obtained thiazole/thiadiazole derived binuclear diaminocarbene complexes (3a EYOVIZ; 3b: EYOWAS; 3d: EYOVOF) suggests that the structures of all these specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…It has been demonstrated that cooperativity, either positive (synergy) or negative (anti‐synergy) is a very important phenomenon in many areas of chemistry 53–64 . Recently, Kukushkin and coworkers 57–64 have observed the existence of noncovalent interactions (hydrogen/halogen/chalcogen/π‐hole bonds) by X‐ray diffraction, investigated the cooperativity between them theoretically by DFT calculations followed by QTAIM analysis, and confirmed experimentally by combined FTIR, HRESI‐MS, 1 H NMR, and diffusion coefficient NMR measurements.…”
Section: Resultsmentioning
confidence: 94%
“…It has been demonstrated that cooperativity, either positive (synergy) or negative (anti‐synergy) is a very important phenomenon in many areas of chemistry 53–64 . Recently, Kukushkin and coworkers 57–64 have observed the existence of noncovalent interactions (hydrogen/halogen/chalcogen/π‐hole bonds) by X‐ray diffraction, investigated the cooperativity between them theoretically by DFT calculations followed by QTAIM analysis, and confirmed experimentally by combined FTIR, HRESI‐MS, 1 H NMR, and diffusion coefficient NMR measurements.…”
Section: Resultsmentioning
confidence: 94%
“…where that the framework of the quantum theory of atoms in molecules (QTAIM) functional is not considered here, which is also a popular method for simulations [90][91][92][93][94][95][96][97][98][99]. The results show that the Hf2CO2/MN heterostructure is formed by vdW interactions [100,101].…”
Section: Resultsmentioning
confidence: 99%
“…MXene/MN , E MXene and E MN show the total energy of the Hf 2 CO 2 /MN heterostructure, monolayered Hf 2 CO 2 and MN, respectively. The smaller the binding energy, the more stable the structure of the heterostructure[89], and thus the most stable structure of those six stacking configurations of the heterostructure is decided as the lowest binding energy, which is demonstrated in the AA stacking style of the Hf 2 CO It is worth not-ing that the framework of the quantum theory of atoms in molecules (QTAIM) functional is not considered here, which is also a popular method for simulations[90][91][92][93][94][95][96][97][98][99]. The results show that the Hf 2 CO 2 /MN heterostructure is formed by vdW interactions[100,101].…”
mentioning
confidence: 99%
“…in these BCPs are typical for non-covalent interactions involving a halogen atom in similar chemical systems [39][40][41] and chalcogen bonds. [42][43][44] Note that Table 2. Values of the density of all electrons -1(r), Laplacian of electron densityr 2 1(r) and appropriate λ 2 eigenvalues, energy density -H b , potential energy density -V(r), and Lagrangian kinetic energy -G(r) (a.u.)…”
Section: Theoretical Studymentioning
confidence: 99%